2017
DOI: 10.1002/smll.201603184
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered Nanoring Arrays Formed by Templated Si‐Containing Triblock Terpolymer Thin Films

Abstract: Laterally ordered nanorings with a periodicity of 38 nm are produced from the directed self-assembly of poly(1,1-dimethylsilacyclobutane)-block-polystyrene-block-poly(methyl methacrylate) thin films on topographically patterned substrates. Such nanoscale arrays with vertically oriented rings are highly desired in technological applications including memory using magnetic recording, metamaterial, waveguide, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 36 publications
3
42
0
Order By: Relevance
“…As the CHCl 3 vapor preferentially attracts the low surface tension block at the film free surface, a PI top‐coat layer on the Q 230 morphology having its (211) plane oriented parallel to the air surface appears as the thermodynamic stable structure on the upper terrace regions of the PS ‐b‐ P2VP ‐b‐ PI layer having a thickness of ≈190 nm. Such a plane orientation, recently observed from solvent‐annealed DG‐forming AB‐type BCP thin films having a low surface energy wetting layer, allows to maximize the area fraction of the low surface energy block at polymer‐air interface as demonstrated by Hashimoto et al Indeed, these authors showed that the area fraction of the minor phase along several crystallographic planes is higher than the BCP chain composition, and decreases as: (210) > (110) > (111) > (100) > BCP chain.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…As the CHCl 3 vapor preferentially attracts the low surface tension block at the film free surface, a PI top‐coat layer on the Q 230 morphology having its (211) plane oriented parallel to the air surface appears as the thermodynamic stable structure on the upper terrace regions of the PS ‐b‐ P2VP ‐b‐ PI layer having a thickness of ≈190 nm. Such a plane orientation, recently observed from solvent‐annealed DG‐forming AB‐type BCP thin films having a low surface energy wetting layer, allows to maximize the area fraction of the low surface energy block at polymer‐air interface as demonstrated by Hashimoto et al Indeed, these authors showed that the area fraction of the minor phase along several crystallographic planes is higher than the BCP chain composition, and decreases as: (210) > (110) > (111) > (100) > BCP chain.…”
Section: Resultsmentioning
confidence: 79%
“…For that purpose, a 2 wt% polymer solution in toluene was spin‐coated on silicon substrates and the film thickness was controlled by the spin‐coating speed (1.5 krpm). The PS‐ b ‐P2VP‐ b ‐PI self‐assembly was achieved by exposing samples to a continuous stream of a CHCl 3 vapor produced by bubbling nitrogen gas through the liquid solvent as described previously . The morphology of the solvent‐annealed PS‐ b ‐P2VP‐ b ‐PI thin films was frozen by quickly removing the lid of the chamber.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] As a result of microphase separation between the different blocks, self-assembled block copolymer thin films into well-ordered nanoscale morphologies [6][7][8] such as spheres, cylinders, lamellae, and complex networks are extremely versatile platforms to achieve well-defined metallic nanostructures. While AB-type block copolymer (BCP) systems offer an attractive route to produce ND arrays with a common p6mm symmetry pattern due to packing frustration, linear ABC triblock terpolymers provide increased accessible structural diversity including core/shell versions of spheres or cylinders (p6mm), [9][10][11][12][13] alternating spheres or cylinders with a tetragonal packing (p2mm), [14,15] and three complex networks with patterns having p4mm, p3m1, or p2 symmetries. [16][17][18][19][20][21] To create metallic ND patterns from self-assembled BCP thin films both ex situ and in situ methodologies have been studied in the literature.…”
Section: Doi: 101002/marc201700754mentioning
confidence: 99%
“…To enlarge the panel of objects attainable from microphase‐separated BCP thin films, linear ABC terpolymers were successfully introduced as patterns . For instance, well‐ordered hexagonal nanoring arrays were fabricated by using linear ABC terpolymers . This appealing nanostructure is highly desired in technological applications since it exhibits unique optical, electronic, and magnetic properties .…”
mentioning
confidence: 99%